Reading Habits and Library Use among Students in Colleges of Education in Ghana: A Case of Two Colleges of Education, Ghana - Kore Appiah, Debora; Kwaah, Christiana Oduraa; Yebowaah, Franklina Adjoa (International Journal of Knowledge Content Development & Technology, 2023)
This paper presents the outcome of a survey done in two colleges of education in Kumasi, Ghana to determine the reading habits of students. A questionnaire was conveniently administered to the third-year students of Wesley College of Education and St. Louis College of Education all in Kumasi the capital of Ashanti Region of Ghana. One hundred and sixty-two copies of the questionnaire were administered to the students in the two colleges. The study found that both parents and tutors influence students reading at the same rate, in both colleges students read an average of one book in two months which was not encouraging with the most preferred reading materials being course books followed by textbooks and fiction. Their purpose of reading is to broaden their knowledge, and to pass examination. They choose busy schedule on campus and too much academic work as the reasons which affect their reading habits. Furthermore, it was revealed that, too much family responsibilities and lack of conducive environment were major constraints that restrict their reading at home. The study recommends the following to enhance reading habits of the students: parents should create healthy surrounding for learning; students should also be motivated to read through the formation of reading clubs and group presentation of assignment.